America's champion swimmer : Gertrude Ederle - Adler, David A.; Widener, Terry (San Diego : Harcourt, 2000)
Describes the life and accomplishments of Gertrude Ederle, the first woman to swim the English Channel and a figure in the early women's rights movement.
"Gulliver books."
580
Accelerated Reader AR
Keywords: Ederle, Gertrude, -- 1906-2003 -- Juvenile literature; Swimmers -- United States -- Biography -- Juvenile literature; Women swimmers -- United States -- Biography -- Juvenile literature